TINJAUAN PROSEDUR PEMBERIAN NOMOR REKAM MEDIS PASIEN DI PUSKESMAS X KOTA KEDIRI - Indah Susilowati (Program Studi Perekam Medis & Informasi Kesehatan, 2022)
The recording of medical record documents at Puskesmas X Kediri City begins with giving a number at the Outpatient Registration Place (TPPRJ) for new patients who register for the first time. Appropriate numbering of medical records helps the process of searching, storing and retrieving medical record documents. The impact of the numbering is not in accordance with the procedure, there will be repetition of the patient's medical record number so that it can eliminate the continuity of the health history and endanger patient safety. The purpose of this study was to determine the procedure for numbering medical records at Puskesmas X, Kediri City. The research method is a qualitative and descriptive approach, using a population and sample of officers at the TPPRJ and standard operating procedures (SOP). The sampling technique was purposive non-random sampling, with officer interviews and observations of the SOP implementation using a checklist sheet. As a result, the medical record numbering system uses the Unit Numbering System. There is a family code, area code, and medical record number in the document for each patient. Providing a new patient's medical record number must match the identity of the name, address and who is the head of the family, and view the Main Patient Index Data on the Computer. The order of medical record numbers is adjusted according to the New Number Control Book. In conclusion, the numbering of medical records at Puskesmas X Kediri has been running well, effectively and in accordance with applicable regulations. The recommended improvement is the creation of a special SOP related to the medical record numbering system, for orderly administration of information accuracy